Computational analysis of three layer fluid model including a nanomaterial layer. (July 2018) - Lu, D.C.; Farooq, U.; Hayat, T.; Rashidi, M.M.; Ramzan, M.
Highlights: Three layer fluid model including a nanomaterial layer is studied. A software package BVPh2.0 solver is used to solve system of coupled nonlinear ordinary differential equations. Convergence of homotopy solutions is demonstrated by average and total squared residual errors. The flow, heat and mass transfer properties are discussed for the physical parameters. Abstract: Multi-layer flows regime occurs in many industrial processes such as petroleum and chemical industry, therefore the study of multi-layer flow in the presence of nanoparticles can be used to obtain desired qualities. This article investigates a vertical three-layer fluid model which incorporates two clear fluid layers and a nanofluid layer which is squeezed between them. A fully developed laminar, incompressible flow field is considered including viscous dissipation effects. The present framework is formulated by capitalizing Buongiorno model which integrate the combined effects of thermophoresis and Brownian motion. The set of ordinary differential equations (ODEs) are non-dimensionalized under appropriate transformations and a nonlinear differential system is than solved by BVPh2.0 solver which is based on an analytical technique named as homotopy analysis method (HAM). Based on the average squared residual error, a procedure for the highly accurate approximation is developed in BVPh2.0. For generalized set of physical parameters it is demonstrated that our obtained solutions are convergent. The influences of governing parameters on the temperature, flow and concentration are analyzed. The result shows a reversed flow for higher values of mixed convection parameter. Furthermore the flow and temperature characteristics at the interface for thermophoresis and Brownian motion parameters are examined numerically.